TYPE 1 DIABETES AND LATENT AUTOIMMUNE DIABETES IN ADULTS: ARE THEY THE SAME? - Nee, Low Yen; Yee, Yoh Yee; Ci, Goh Qing; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION It is believed that LADA is the extreme end of T1DM as they shared similarities in terms of genetic susceptibility and presence of similar islet autoantibodies but presented in the older age. METHODOLOGY This is a cross-sectional study based in T1DM Clinic, Hospital Melaka where patients’ information was collected via records and latest clinic visits. We aimed to compare T1DM and LADA patients in terms of phenotype, complications, co-morbidities and treatment. RESULTS We had 95 T1DM patients and 27 LADA patients in our clinic. LADA patients were older (54 + 15 years old vs 28 + 17 years old, P<0.001) with later onset (43 + 15 years old vs 15 + 10 years old, P<0.001) compared to T1DM patients. Less LADA patients had diabetic ketoacidosis as the initial presentation but it is associated with higher rates of hypertension (44.4% vs 21.1%, P=0.015) and dyslipidemia (77.8% vs 36.8%, P<0.001). LADA patients had lower eGFR (90.4 + 35 mls/min vs 111.0 + 30.6 mls/min, P=0.001) and higher rate of ischemic heart disease (14.8% vs 3.2%, P=0.042). Treatment wise, more LADA patients were on oral hypoglycemic agent (44.4% vs 20%, P=0.01), anti-hypertensives (59.3% vs 37.9%, P=0.048) and statins (81.5% vs 34.7%, P<0.001) but required less total daily dose of insulin per weight (0.60 + 0.23 u/kg/day vs 0.75 + 0.30 u/kg/day, P=0.006). There was no significant statistical difference in HbA1c between both groups. CONCLUSION Early recognition of LADA patients and intensive glycemic management in this group of patients may be crucial as they can present with more complications compared to T1DM patients.